2015
DOI: 10.1039/c5dt02484f
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-radiolytic stability of new methylated TODGA derivatives for minor actinide recycling

Abstract: The stability against gamma radiation of MeTODGA (methyl tetraoctyldiglycolamide) and Me2TODGA (dimethyl tetraoctyldiglycolamide), derivatives from the well-known extractant TODGA (N,N,N',N'-tetraoctyldiglycolamide), were studied and compared. Solutions of MeTODGA and Me2TODGA in alkane diluents were subjected to (60)Co γ-irradiation in the presence and absence of nitric acid and analyzed using LC-MS to determine their rates of radiolytic concentration decrease, as well as to identify radiolysis products. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
67
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 29 publications
11
67
1
Order By: Relevance
“…These have included studies of the radiation chemistry of tetraoctyldiglycolamide (TODGA) and tetra(2-ethylhexyl)diglycolamide (TEHDGA), [7] didodecyldioctyldiglycolamide (D 3 DODGA), [8] and methyl-tetraoctyldiglycolamide (Me-TODGA) and dimethyl-tetraoctyldiglycolamide (Me 2 -TODGA). [9] Unlike many other fuel cycle ligands, all the lipophilic DGAs in dodecane diluent were degraded by irradiation with about the same dose constant (kGy -1 ), and that rate did not vary significantly in the presence or absence of contact with aqueous phases of varying acidity. Common products of irradiation were trialkyldiglycolamides produced by loss of an alkane group from one of the N-atoms, production of carboxylic acids following C-N bond rupture with loss of the amine group, and acetamides and glycolamides resulting from rupture of the central ether linkage.…”
Section: Introductionmentioning
confidence: 97%
“…These have included studies of the radiation chemistry of tetraoctyldiglycolamide (TODGA) and tetra(2-ethylhexyl)diglycolamide (TEHDGA), [7] didodecyldioctyldiglycolamide (D 3 DODGA), [8] and methyl-tetraoctyldiglycolamide (Me-TODGA) and dimethyl-tetraoctyldiglycolamide (Me 2 -TODGA). [9] Unlike many other fuel cycle ligands, all the lipophilic DGAs in dodecane diluent were degraded by irradiation with about the same dose constant (kGy -1 ), and that rate did not vary significantly in the presence or absence of contact with aqueous phases of varying acidity. Common products of irradiation were trialkyldiglycolamides produced by loss of an alkane group from one of the N-atoms, production of carboxylic acids following C-N bond rupture with loss of the amine group, and acetamides and glycolamides resulting from rupture of the central ether linkage.…”
Section: Introductionmentioning
confidence: 97%
“…The radiation-induced hydrolysis, as one of the main processes resulting in loss of the extraction ability upon irradiation, is also typical for aliphatic amides, such as malonamides 37 and diglycol amides. 5 Samples irradiated in the presence of nitric acid contained a variety of degradation products similar to the case of ageing, including substance IV that was established for 6 M nitric acid solution. In contrast to the samples that had no contact with nitric acid, there was no signicant amount of hydrolysis products, which evidences about hydrolysis suppression by nitric acid under gamma-irradiation.…”
Section: Esi-ms Analysis Of Radiolysis Productsmentioning
confidence: 99%
“…Earlier, the radiolytic stability of a number of extraction systems developed for both the group separation of An(III)/Ln(III) and their individual element's separation has been studied in details. [3][4][5][6][7] The classical experimental approach for testing of the radiation stability is an external gamma irradiation of organic extractant solutions, subsequent extraction experiments and determination of qualitative and quantitative composition of radiolysis products. However only few studies were performed on the theoretical predictions of irradiation effects and the most radiation-stable ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that an alkyl substituent at the backbone also has a considerable influence. 2,3 The extraction properties are considerably improved in case of tripodal DGAs 4 or when the DGA units are appended to a calix[4]arene skeleton. 5 Sasaki et al 6 prepared a series of DGAs with varying alkyl groups at the amidic nitrogen atoms by reaction of diglycolic anhydride with one equivalent of an amine.…”
mentioning
confidence: 99%